2018
DOI: 10.12691/jfnr-6-7-5
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Antioxidant Capacity of Human Milk after Freezing and Pasteurization

Abstract: Pasteurization and freezing are processes used in human milk banks that can affect some of the nutritional and biological properties of human milk. The aim of this study was to evaluate impact of the processing steps adopted by human milk banks on the contents of total phenolic compounds and antioxidant capacity in vitro. Experimental study was realized, in which 40 mL human milk were collected from 8 mothers registered at the Human Milk Bank of Ouro Preto, state of Minas Gerais. Samples were homogenized to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The studies included in this review used several pasteurization methods. Thermal processing is the most commonly used pasteurization method, with Holder pasteurization as the gold standard described most frequently [ 6 , 13 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. During Holder pasteurization, human milk is heated in a water bath to 62.5 °C for 30 min, and subsequently cooled to approximately 4 °C [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies included in this review used several pasteurization methods. Thermal processing is the most commonly used pasteurization method, with Holder pasteurization as the gold standard described most frequently [ 6 , 13 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. During Holder pasteurization, human milk is heated in a water bath to 62.5 °C for 30 min, and subsequently cooled to approximately 4 °C [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Different methods to determine the TAC are described in the literature such as: Trolox equivalent antioxidant capacity (TEAC), ferric reducing ability of plasma (FRAP), and cupric reducing antioxidant capacity (CUPRAC) [ 35 ]. In the included studies, the most frequently described method was the TEAC assay, which measures the TAC by scavenging 2,2-azinob-bis 3 ethylbenzthiazoline-6-sulfonic acid radicals (ABTS) [ 14 , 21 , 23 , 24 , 25 ]. Moreover, two studies used the DPPH assay, which measures the TAC by scavenging 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radicals [ 14 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a negative effect of the pasteurization process followed by the freezing of breast milk was observed on the content of total phenolics, accompanied by a consequent decrease in the total antioxidant capacity in the first seven days of storage. 18 Breast milk contains numerous antioxidant peptide precursor proteins, very important for the control of EO, which occurs even in normal situations and is aggravated in situations of stress, low birth weight and in cases of admission to the Neonatal Intensive Care Unit (NICU), in which the use of pasteurized breast milk is necessary, when expressed breast milk is not sufficient. Premature infants are specifically sensitive to free radicals because of some peculiar situations, such as hypoxic-hyperoxic challenge, infections, deficiency in antioxidant defense and high levels of free iron.…”
Section: Discussionmentioning
confidence: 99%
“…To estimate variability for this characteristic, it was based on Nogueira et al, who obtained a standard deviation of approximately 10 microMol for the total antioxidant activity test (ABTS). 18 For dimensioning, a significance level of 5%, power of 80%, magnitude of effect of 9 microMol and paired Student's t-test as an inferential test, reaching the minimum size of 18 samples when applying the formula.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, studies have shown that slow pasteurization leads to reduced levels of some of the antioxidant components present in HM such as glutathione peroxidase (Silvestre et al, 2008), vitamin C (Moltó-Puigmartí et al, 2011, total antioxidant capacity (Nogueira et al, 2018;Silvestre et al, 2008) In this context, innovative methods of food preservation such as ultrasound (US), high pressure, ionizing radiation, pulsed electric field, microfiltration and ultraviolet radiation, have been tested as possible alternatives to conventional thermal treatments in order to maintain microbiological safety with less impact on nutritional, functional and sensory aspects (Monteiro et al, 2020;Shabbir et al, 2020;Jasmi et al, 2020;Awad et al, 2012). In this context, the treatment of food with ultrasound (US) can offer an alternative to traditional methods (Piñon et al, 2019;Fernández-Barbero et al, 2019).…”
Section: Impact Of Ultrasound Treatment On Viability Of Staphylococcus Aureus and The Human Milk Antioxidant Activitymentioning
confidence: 99%